2018
DOI: 10.1021/acs.bioconjchem.7b00774
|View full text |Cite
|
Sign up to set email alerts
|

SN-38 Conjugated Gold Nanoparticles Activated by Ewing Sarcoma Specific mRNAs Exhibit In Vitro and In Vivo Efficacy

Abstract: The limited delivery of chemotherapy agents to cancer cells and the nonspecific action of these agents are significant challenges in oncology. We have previously developed a customizable drug delivery and activation system in which a nucleic acid functionalized gold nanoparticle (Au-NP) delivers a drug that is selectively activated within a cancer cell by the presence of an mRNA unique to the cancer cell. The amount of drug released from sequestration to the Au-NP is determined by both the presence and the abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Interesting studies were carried by Naumann et al [ 120 ]. The team employed SN-38 conjugated to gold nanoparticles via oligonucleotides complementary to specific mRNAs unique to the cancer cells of Ewing sarcoma.…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting studies were carried by Naumann et al [ 120 ]. The team employed SN-38 conjugated to gold nanoparticles via oligonucleotides complementary to specific mRNAs unique to the cancer cells of Ewing sarcoma.…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…In a cancer cell, the SN38-conjugate oligonucleotide is released, allowing the inhibition of topoisomerase by SN-38. The obtained result showed that the drug was efficiently delivered and selectively released in both in vitro and in vivo conditions [ 120 ].…”
Section: New Irinotecan Formulationsmentioning
confidence: 99%
“…Furthermore, the dimeric prodrugs could respond to the high glutathione (GSH) level of the tumor, to produce active monomeric drugs. SN38 is an active metabolite of camptothecin in vivo, and works on DNA topoisomerase for cancer cells killing . LND, a hexokinase inhibitor, exhibits antitumor activity by impacting energy metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles have gained significant attention in recent years as nanocarriers due to their tunable size, flexibility of surface functionalization, and modifiable rate of cellular uptake which depend on the surface functionaliza- tion. 54,55) A recent study by Lee et al demonstrated HDR of the DMD-associated, C-X-C motif chemokine receptor 4 (CXCR4) gene using a gold nanoparticle-polymer complex. 56) This vehicle was composed of a 15 nm gold core conjugated with thiol-modified oligonucleotides and complexed with donor DNA.…”
Section: Non-viral Delivery Methodsmentioning
confidence: 99%